Metodologi al-Asha‘irah dan al-Salafiyyah Dalam Membentangkan Akidah al-Qada’ dan al-Qadar: Tinjauan Awal Terhadap Maratib al-Taqdir: Methodology of al-Asha‘irah and al-Salafiyyah in Presenting the ‘Aqidah of al-Qada’ and al-Qadar: The Early Review on Maratib al-Taqdir - Mohd Azhar, Muhammad Hazim; Syed Abdul Rahman, Syed Mohammad Hilmi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
The belief in al-Qada’ and al-Qadar is one of the Pillars of Faith that is mandatory for every Muslim to recognize. Deviation of this belief may lead a person to the abyss of infidelity and disbelief. Hence, the scholars try to study, compile and formulate the concept of al-Qada’ and al-Qadar for society to better understand it. Utilizing comparative methods, this article compares, integrates and assimilates the methodology of presentation and affirmation the belief of al-Qada’ and al-Qadar according to al-Asha‘irah and al-Salafiyyah. In the works of al-Asha‘irah regarding faith, the essential components of al-Qada’ and al-Qadar can be viewed in the scopes of Ilahiyyat within the discussion of the attributes of Allah and His actions. The debate is more load up with proofs of reason as a formula for answers to doubt. According to al-Salafiyyah, al-Qada’ and al-Qadar debates are exemplified by the presentation of the Maratib sub-topic or Arkan al-Taqdir by focusing on the proof of the texts without emphasis on the detailed aspects of interpretation.